Twórca wobec przestrzeni i czasu. Przyczynek do rozważań o filozofii mobilności Andrzeja Stasiuka - Setlak, Wiesław (Tematy i Konteksty, 2015)
For the last decade Andrzej Stasiuk’s prose has focused on description and interpretation of the author’s numerous journeys to central and Eastern European countries, the Balkans and Asia. He talks about them with his characteristic literary disposition, thus creating a specific genre which can be defined as ‘a wanderer’s diary’ or ‘travel story’. In such works as 'Going to Babadag' (2006), 'There are no expresses by the yellow roads' (2013) or 'The East' (2014), the relational layer maintained in the convention of literary reportage co-exists in an active way with the reflective layer, the artistic projection of which is the clearly marked cultural and spatial nature and the teleology of dynamic existence within its frame requires intellectual mobility in comparing distinguishing features of the Oriental and Occidental cultural systems. The author is clearly in favour of the former – it is the basic territory of his existence as a human being and an artist. Andrzej Stasiuk’s philosophy of mobility marked by nomadic thinking obviously clashes with the desire for balance in the world and his intellect rejects both the opportunity of ‘an escape to the utopia’ and acceptance of what is happening in his territory.